Stimulasi Dini Sebagai Strategi Promotif Preventif Serta Peranan Orang Tua dalam Peningkatan Tumbuh Kembang Anak - Riama Claudia Christine Lumban Gaol; Nur Alam Fajar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The growth and development of childrens’s brain develops very quickly during the golden periode. This golden age starts from birth until the child is 4 years old. Children will be very quickly receive stimuli from the surrounding environment at this time. Parents often do not realize that their child is experiencing delays in growth and development. Parents can use early stimulation as a promotive and preventive strategy to improve the quality of their child’s growth and development. This research aims to describe promotive and preventive strategy through early stimulation and the role of parents in improving the quality of childrens’s growth and development. The researcher used a qualitative method, a literature study approach, which went through an interactive analysis stage including the data collection stage, data reduction stage, data verification stage, and data presentation stage. The results of the analysis draw a conclusion that early stimulation can be a promotive and preventive strategies in improving the quality of children’s growth and development and in the process, the involvement of parents is very important.